Wulandari, Sri OPTIMALISASI DESAIN GROOVE UNTUK MENINGKATKAN KINERJA BUSHING PADA RODA BOGIE BERBASIS SIMULASI CFD - wulandari, Sri Wulandari; Fatahul Arifin; Irawan Malik (MACHINERY Jurnal Teknologi Terapan, 2024)
Optimization is a process of maximizing an object to find the best results from a set of alternative solutions that exist, so as to increase its effectiveness, such as profits, minimize process time and so on. This thesis aims to conduct CFD (Computational Fluid Dynamics) simulation analysis on bushings with different grooves in an effort to improve lubrication efficiency. This research uses CFD (Computational Fluid Dynamics) simulation analysis on bushings with different grooves in an effort to improve lubrication efficiency. This research uses CFD (Computational Fluid Dynamics) simulation where a method is used to model, analyze, and related phenomena in the system using a numerical approach. The addition of grooves or grooves on the bushing surface can affect the flow of lubricant around it. Through CFD simulation, the author will compare the performance of various groove designs to identify models that provide better lubrication. The results of this research are expected to provide valuable insights in the development of more lubrication-efficient bushings.